Pemberdayaan Masyarakat dalam Penyusunan Program Pemanfaatan dan Penanaman TOGA - Silfa Ayu Safika; Rina Tri Agustini; Lies Permana (Jurnal Pengabdian Pada Masyarakat, 2022)
COMMUNITY EMPOWERMENT IN THE PREPARATION OF TOGA UTILIZATION AND PLANTING PROGRAMS. The community of the RT 29 area have a tendency to use traditional medicine, especially herb and spice plants. However, the local community is still processing spice plants empirically and there is no management of the Family Medicine Garden (TOGA) in the area around the community settlements. The purpose of this community empowerment is to enable the community of RT 29 Sidodamai Village in the proper use of herb and spice plants as traditional medicine through education, the establishment of a TOGA cadre communication forum, and the preparation of a follow-up plan for TOGA planting. The implementation of activities in community empowerment uses the Participatory Rural Action (PRA) method which is carried out in 6 stages, i.e. community introduction, problem introduction, problem awareness, program implementation and program evaluation. The programs carried out included discussions, health education, mentoring TOGA cadres and the preparation of follow-up plans in the form of planting TOGA in RT 29. The results of this series of activities were that there was knowledge after being given health education material on the use of herb and spice plants, the existence of a communication forum for TOGA cadres with the Puskesmas Sidomulyo in planning the follow-up plan, and the independence of the community in carrying out the preparation for TOGA planting activities according to the planned schedule.